The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/land11122168
|View full text |Cite
|
Sign up to set email alerts
|

Ranking of Empirical Evapotranspiration Models in Different Climate Zones of Pakistan

Abstract: Accurate estimation of evapotranspiration (ET) is vital for water resource development, planning and management, particularly in the present global warming context. A large number of empirical ET models have been developed for estimating ET. The main limitations of this method are that it requires several meteorological variables and an extensive data span to comprehend the ET pattern accurately, which is not available in most developing countries. The efficiency of 30 empirical ET models has been evaluated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 99 publications
(108 reference statements)
1
3
0
Order By: Relevance
“…The statistical results of the eight empirical models (Dal1802, Trab1896, Harg1975, Irs2003, HargS1985, BC1986, VAL2013a and VAL2013b) for estimating daily RET at the five meteorological stations within the Gharb and Loukkos perimeters are presented in Tables 8 and 9 outperform radiation-based models like Harg1975 and Irs2003, as well as mass transfer models like Dal1802 and Trab1896. This finding is in line with the conclusions drawn by several other researchers [11]. Conversely, it is important to note that some researchers [14,55,57] have suggested that radiationbased models may perform better than temperature-based models.…”
Section: Empirical Models' Comparison For Daily Reference Evapotransp...supporting
confidence: 91%
See 2 more Smart Citations
“…The statistical results of the eight empirical models (Dal1802, Trab1896, Harg1975, Irs2003, HargS1985, BC1986, VAL2013a and VAL2013b) for estimating daily RET at the five meteorological stations within the Gharb and Loukkos perimeters are presented in Tables 8 and 9 outperform radiation-based models like Harg1975 and Irs2003, as well as mass transfer models like Dal1802 and Trab1896. This finding is in line with the conclusions drawn by several other researchers [11]. Conversely, it is important to note that some researchers [14,55,57] have suggested that radiationbased models may perform better than temperature-based models.…”
Section: Empirical Models' Comparison For Daily Reference Evapotransp...supporting
confidence: 91%
“…𝑥 𝑛𝑜𝑟𝑚 = 𝑥 0 − 𝑥 𝑚𝑖𝑛 𝑥 𝑚𝑎𝑥 − 𝑥 𝑚𝑖𝑛 (11) Where, xnorm represents the normalised value, x0 is the real value, and xmin and xmax are the minimum and maximum values respectively.…”
Section: Weighted Hybridization For ML Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last century, Pakistan's average temperature has risen by over 0.6°C, with more significant increases observed in the northern, high‐elevated areas. Moreover, the increase was more pronounced in the second half (1951–2000) than in the first half (1901–1949) (Ali et al, 2019; Hamed et al, 2022a). These variations in temperature and precipitation variables are worth studying for the water resource management of the region.…”
Section: Introductionmentioning
confidence: 99%